A CoSe–C@C core–shell structure with stable potassium storage performance realized by an effective solid electrolyte interphase layer. Issue 18 (29th April 2021) - Gu, Xin; Zhang, Li; Zhang, Wenchao; Liu, Sailin; Wen, Sheng; Mao, Xinning; Dai, Pengcheng; Li, Liangjun; Liu, Dandan; Zhao, Xuebo; Guo, Zaiping
Abstract : A CoSe–C@C core–shell structure is designed as a novel potential anode for PIBs. The introduction of KFSI salt is found to contribute to the formation of an inorganic-compound-rich SEI layer, benefiting the K ion diffusion and charge transfer dynamics. Abstract : Conversion/alloying materials with high theoretical capacity are promising for potassium-ion batteries, although their development is seriously blocked owing to their volume expansion and ineffective solid-electrolyte interphase (SEI) protection. Herein, it is discovered that the performance of the CoSe anode material could be enhanced through a flexibly designed core–shell structure (denoted as CoSe–C@C) and an inorganic compound-rich SEI. The CoSe–C@C electrode exhibits stable cycling performance (432 mA h g −1 at 200 mA g −1 ) over 1000 cycles and outstanding rate capability (233 mA h g −1 at 10 A g −1 ). A reversible conversion mechanism for the potassiation/depotassiation in CoSe is revealed by ex situ X-ray diffraction patterns and high-resolution transmission electron microscope images, while the SEI on the CoSe–C@C surface is found to be inorganic-rich (KF-), which is favourable for K ion diffusion and charge transfer dynamics. These findings would shed light on nanostructure design strategies and our fundamental understanding of the SEI formation in electrolyte engineering for potassium-ion batteries.